Positive Politeness Strategies Analysis in the Court Situation: Caught in Providence YouTube’s Video Welcome to America - Mawaddah, Tiar Aulia; Cahyono, Setyo Prasiyanto (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Politeness strategies are the ways that used by someone to convey their speech when having a conversation with others [Saputra, Lubis, Setiawan, 2021]. Politeness strategies can be observed in everyday’s life also in similar circumstances but in different situations, namely in the judicial process. This study aims to find and examine positive politeness strategies used by the judge and the defendant in court room entitled “Welcome to America!”. In this study, the researchers apply qualitative method by describing the phenomenon of the data. The source of the data in this study was gained from a YouTube channel account “Caught in Providence”. "Welcome to America” is ​​about the court situation for traffic violations committed by a Syrian citizen who has lived in America for 3 years. Meanwhile, in analyzing the data, the researchers employ a framework proposed by Brown and Levinson [1987]. The result of this study shows that there were found fifteen types of positive politeness strategies used by the speakers. However, the most commonly positive politeness produced by the speakers are strategy 7 Presuppose/raise/assert common ground, there are seven sub-strategies. They are personal centre-switch, the usage of tag question, place switch, presuppose knowledge of hearer’s wants, presuppose familiarity, presuppose hearer’s knowledge, and the usage of pronoun that hasn’t been made clear and strategy 2: Exaggerate (interest, approval, sympathy with hearer) In this case, the judge wants to convince the defendant to obey the rules also give the sympathy to the defendant because of their manners and the reasons for the violation can still be considered. The fifteen types of positive politeness strategies serve to analyze the utterance was expressed between the judge and the defender in the judicial process.